N‐Type Surface Doping of MAPbI3 via Charge Transfer from Small Molecules. (10th June 2018) - Perry, Erin E.; Labram, John G.; Venkatesan, Naveen R.; Nakayama, Hidenori; Chabinyc, Michael L.
Abstract: Organic hole and electron transport materials are regularly employed as electron‐ and hole‐blocking layers in perovskite thin‐film solar cells. In order to optimize charge extraction in the device, these organic layers can be doped using organic small molecules. However, to date there is little work carried out on direct doping of perovskite surfaces. In this report, the change in electrical properties of thin films of MAPbI3 by surface doping the film with an organic dopant molecule: cobaltocene (Co(C5 H5 )2 ) is studied. By varying the quantity of cobaltocene deposited, the conductivity of MAPbI3 thin films is observed to be tunable over several orders of magnitude. A tunable shift in the Fermi level illustrating that charge transfer doping enables control over the interfacial energy levels, is observed. An increase in photoconductivity is seen at intermediate doping levels, indicating passivation of surface traps confirmed by increased photoluminescence. This model system provides a means to understand more complex heterointerfaces of doped organic blends at perovskite surfaces. Abstract : Surface doping of methylammonium lead iodide (MAPbI3 ) can be achieved by electron transfer from cobaltocene (Co(C5 H5 )2 ). By varying the quantity of Co(C5 H5 )2 deposited from solution, the degree of n ‐type charge transfer to the surface of MAPbI3 can be controlled and surface traps can be passivated.